The effect of glutamine administration on urinary ammonium excretion in normal subjects and patients with renal disease - Welbourne, Tomas (1972)
The effect of acute changes in the delivery rate of glutamine to the kidney on urinary ammonium excretion was studied in man. Healthy subjects and patients with intrinsic renal disease were studied under three different acid-base conditions: unaltered acid-base balance; NH(4)Cl-induced acidosis; and NaHCO(3)-induced alkalosis. Anhydrous L-glutamine was administered orally in a single dose of 260 mmoles during each of these three acid-base states. We found that endogenous venous plasma glutamine concentration fell during acidosis and rose during alkalosis in both healthy subjects and patients with renal disease. In healthy subjects, orally administered glutamine raised plasma glutamine concentration markedly over a 2-3 hr period. This was accompanied by an increase in urinary ammonium excretion and a rise in urine pH under normal acid-base conditions and during metabolic acidosis. No increase in ammonium excretion occurred when glutamine was administered during metabolic alkalosis in spite of an equivalent rise in plasma glutamine concentration. In patients with renal disease, endogenous venous plasma glutamine concentration was lower than in healthy subjects, perhaps as a result of mild metabolic acidosis. Acute oral glutamine loading failed to increase urinary ammonium excretion significantly during either unaltered acid-base conditions or after NH(4)Cl-induced acidosis, even though plasma glutamine rose as high as in healthy subjects. We conclude from these observations that glutamine delivery to the kidney is a rate-limiting factor for ammonium excretion in healthy subjects, both before and after cellular enzyme adaptation induced by metabolic acidosis. In contrast, in patients with renal disease, glutamine delivery is not rate-limiting for ammonium excretion. Presumably other factors, such as surviving renal mass and the activity of intracellular enzymes necessary for ammonia synthesis limit ammonium excretion in these patients.